Universities of the Russian empire in the life and works of M. Kostomarov - Bohdashyna, Olena (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2022)
The purpose of the article is to determine the role of Universities of the Russian Empire in the life and work of the famous historian and ethnographer M. Kostomarov, and on the other hand to show how his multilateral activities influenced the development of the higher education system in the country. This analysis is accompanied by our comments on discrepancies in biographical facts in sources and literature. The research methodology consists of general scientific principles of historicism and objectivity, special historical methods, in particular problem-chronological, problem-historiographic, historical-comparative, historical-genetic , historical-typological, as well as biographical approach. Scientific novelty. The role of Universities of the Russian Empire in the life and work of the famous historian and ethnographer M. Kostomarov is clarified; the influence of his pedagogical work on the higher education in the country is shown; several discrepancies in the sources are commented on. The results. The article examines the role of universities of the Russian Empire in the life and work of the famous historian and ethnographer M. Kostomarov. In particular, the role of Kharkiv University in the formation of M. Kostomarov as a young scientist is shown in detail. Kharkiv University played the greatest role in the development of M. Kostomarov as the scientist. M. Kostomarov’s studies at this university, and especially the defense of both master’s theses of the young scientist, were accompanied by artificial obstacles. Not only ill-wishers, but also M. Kostomarov himself is to blame for creating problems (with obtaining a candidate’s diploma, with defending both master’s theses. A certain role in the intellectual biography of M. Kostomarov was played by Moscow University. M. Kostomarov’s listening to lectures by Moscow university professors in 1838 was temporary and situational. In our opinion, this was a search for support among the local professorship in a scientific career, in the preparation and defense of a master’s thesis. Short periods of lecturing at Kiev (1846-1847) and St. Petersburg (1859-1862) universities were held in more favorable conditions. But the termination of teaching at the Kiev University of St. Vladimir logically ended with the arrest in the case of the Secret Society of Cyril and Methodius. Kostomarov’s lecturing activity at St. Petersburg University ended with a student boycott. In our opinion, both sides were guilty of the conflict. The unreliable historian’s attempts to find a job after exile at Kazan, Kharkiv and Kiev universities were unsuccessful due primarily to subjective factors. These difficulties enriched his life experience, allowed him to get to know the academic environment better, showed him that scientific activity is inseparable from struggle in a professional environment. Kostomarov devoted his life to education and science. 5 universities of the Russian Empire played a role in the life of an outstanding historian, in three of them he managed to work. For a teacher and scientist, university life is the main, most valuable part of his intellectual biography. At the same time, М. Kostomarov’s teaching activity has become an important fragment in the history of the above-mentioned universities.